The social protection indicator for the Pacific assessing progress. - Asian Development Bank (Manila,Philippines Asian Development Bank, [2019])
It presents an analysis of 2015 data on social protection programs, particularly the substantial progress in expenditure and benefit size between 2009 and 2015. Yet, spending favored the nonpoor over the poor, and the gap in spending on men and on women widened. The Social Protection Index now the Social Protection Indicator was developed by ADB and its partners as the first comprehensive and quantitative measure of social protection systems in Asia and the Pacific.
Keywords: Social security -- Pacific Area; Public welfare -- Pacific Area; Pacific Area -- Social policy; Electronic book